New records of the Paleotropical migrant Hemianax ephippiger in the Caribbean and a review of its status in the Neotropics. Issue 4 (1st October 2020) - Hedlund, Johanna; Ehrnsten, Eva; Hayward, Christina; Lehmann, Philipp; Hayward, Alex
Abstract : Tropical America is currently experiencing the establishment of a new apex insect predator, the Paleotropical dragonfly Hemianax ephippiger (Odonata: Aeshnidae). H. ephippiger is migratory and is suggested to have colonised the eastern Neotropics by chance Trans-Atlantic displacement. We report the discovery of H. ephippiger at three new locations in the Caribbean, the islands of Bonaire, Isla de Coche (Venezuela), and Martinique, and we review its reported distribution across the Neotropics. We discuss the establishment of H. ephippiger as a new apex insect predator in the Americas, both in terms of ecological implications and the possible provision of ecosystem services. We also provide an additional new species record for Bonaire, Pantala hymenaea (Odonata: Libellulidae).